Liquid Nickel Salts: Synthesis, Crystal Structure Determination, and Electrochemical Synthesis of Nickel Nanoparticles. Issue 3 (8th December 2015) - Sniekers, Jeroen; Verguts, Ken; Brooks, Neil R.; Schaltin, Stijn; Phan, Thanh Hai; Trung Huynh, Thi Mien; Van Meervelt, Luc; De Feyter, Steven; Seo, Jin Won; Fransaer, Jan; Binnemans, Koen
Abstract: New nickel‐containing ionic liquids were synthesized, characterized and their electrochemistry was investigated. In addition, a mechanism for the electrochemical synthesis of nanoparticles from these compounds is proposed. In these so‐called liquid metal salts, the nickel(II) cation is octahedrally coordinated by six N ‐alkylimidazole ligands. The different counter anions that were used are bis(trifluoromethanesulfonyl)imide (Tf2 N − ), trifluoromethanesulfonate (OTf − ) and methanesulfonate (OMs − ). Several different N ‐alkylimidazoles were considered, with the alkyl sidechain ranging in length from methyl to dodecyl. The newly synthesized liquid metal salts were characterized by CHN analysis, FTIR, DSC, TGA and viscosity measurements. An odd‐even effect was observed for the melting temperatures and viscosities of the ionic liquids, with the complexes with an even number of carbon atoms in the alkyl chain of the imidazole having a higher melting temperature and a lower viscosity than the complexes with an odd number of carbons. The crystal structures of several of the nickel(II) complexes that are not liquid at room temperature were determined. The electrochemistry of the compounds with the lowest viscosities was investigated. The nickel(II) cation could be reduced but surprisingly no nickel deposits were obtained on the electrode. Instead, nickel nanoparticles were formed at 100 % selectivity, as confirmed by TEM. The magnetic properties of these nanoparticles were investigated by SQUID measurements. Abstract : Liquid bunch : Several new liquid nickel(II) salts were synthesized, characterized by XRD, and tested for the electroreduction of nickel. Nickel nanoparticles were formed at 100 % selectivity, as was characterized by TEM and SQUID measurements. A mechanism for the electrochemical synthesis of nanoparticles is proposed.